2013
DOI: 10.1111/dote.12064
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic dilation versus laparoscopic Heller myotomy for the treatment of achalasia: variables related to a good response

Abstract: Achalasia is a motor disorder characterized by esophageal aperistalsis and failure of lower esophageal sphincter relaxation. The cardinal symptoms are dysphagia, food regurgitation and weight loss. The most effective treatments are pneumatic dilation (PD) of the cardia and Heller esophageal myotomy with partial fundoplication. There is still controversy regarding which treatments should be initially done. The aims of this study were to evaluate clinical response and the variables related to good results in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 33 publications
0
39
1
1
Order By: Relevance
“…and follow treatment outcomes 25 . While these tests are also used to monitor treatment response, a self-reported measure of symptom severity is often the primary outcome in clinical studies and is often the principal factor that drives clinical management decisions 2, 68 .…”
Section: Introductionmentioning
confidence: 99%
“…and follow treatment outcomes 25 . While these tests are also used to monitor treatment response, a self-reported measure of symptom severity is often the primary outcome in clinical studies and is often the principal factor that drives clinical management decisions 2, 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the excellent short‐term success rate that was achieved in more than 90% of patients undergoing PD, recurrence of symptoms could occur in approximately 20% in 2 years, 30% in 5 years and about 40% in 10 years after the procedure . Controversy regarding the therapy for achalasia patients with failed PD still exists.…”
Section: Introductionmentioning
confidence: 99%
“…In 4 other studies, symptom evaluation was based on various dysphagia scores. In the studies by Hamdy et al [23] and Borges et al [18] the primary outcome was the successful symptomatic improvement, which used the Demeester's or Vantrappen and Hellemans dysphagia score. In the studies by Persson et al [24] and Kostic et al [25] the primary end point was the cumulative number of treatment failures.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis included 360 patients in the balloon dilation group and 389 in the Heller myotomy group. One study (Borges et al) [18] reported significant differences in the patients' ages between the two treatment groups, but in the other 7 studies no significant difference was found in this regard. The data published in 8 studies assessing the distribution of genders showed no difference between the two groups.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 96%
See 1 more Smart Citation